Automated Administrative Orders in Lithuania - Strikaitė-Latušinskaja, Goda (Teisė, 2022)
By analyzing various sources of law, this paper provides an assessment of the method of automated administrative order that is used in Lithuania, its potential problematic risks, determined due to the chosen legal regulation, as well as the European vision of integrating technology in the implementation of the public functions of the state. After evaluating the provisions of both national law and European Union law, a proposal regarding how to improve the chosen method of incorporating algorithms into the process of adopting certain administrative orders is made.